2017
DOI: 10.1186/s13019-017-0648-7
|View full text |Cite
|
Sign up to set email alerts
|

A dual therapy of off-pump temporary left ventricular extracorporeal device and amniotic stem cell for cardiogenic shock

Abstract: BackgroundTemporary mechanical circulatory support device without sternotomy has been highly advocated for severe cardiogenic shock patient but little is known when coupled with amniotic stem cell therapy.Case presentationThis case reports the first dual therapy of temporary left ventricular extracorporeal device CentriMag with distal banding technique and human amniotic stem cell injection for treating a severe refractory cardiogenic shock of an 68-year-old female patient. A minimally-invasive off-pump LVAD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Other countries followed suit and in the ensuing 15 years, an additional seven case reports or case series (41)(42)(43)(44)(45)(46)(47), a single randomized multicenter trial (48) and two nonrandomized clinical trials (26,49) have been reported to date around the world.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other countries followed suit and in the ensuing 15 years, an additional seven case reports or case series (41)(42)(43)(44)(45)(46)(47), a single randomized multicenter trial (48) and two nonrandomized clinical trials (26,49) have been reported to date around the world.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Kazui et al were the first to attempt concurrent LVAD implantation and intramyocardial injection of allogenic amniotic stem cells, resulting in the only North American study to date that demonstrated successful ventricular recovery to allow for LVAD withdrawal after 3 weeks.…”
Section: Clinical Studiesmentioning
confidence: 99%